THE IMPORTANT ROLES OF TEACHERS IN ENGLISH LANGUAGE TEACHING (ELT) - Umar Umar (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2021)
the aim of this reseach is to find elaborate the roles of teachers in English language teaching (ELT. Starting from free trade, the increasing number of foreign companies established in Indonesia, so that the use of international languages such as English is very widespread. Of course, aspiring entrepreneurs and job seekers have to master English so they can keep up with the times in this globalization era. If you are still in school or college, then you have the opportunity to learn and master English. If you have graduated from school or college, you should be ready to enter the world of work with the English skills needed by your place of work. To acquire good communication skills or to excel in communication skills, one has to acquire expertise in all the four skills. They are Listening, Speaking, Reading and Writing. Before students are able to master these 4 skills, students have to develop interest towards the subject or language. This is where the important role of the teacher will appear.